2021
DOI: 10.1016/j.ekir.2021.03.331
|View full text |Cite
|
Sign up to set email alerts
|

POS-315 The Study of DNA Methylation and Some Potential Environmental Pollutants in Patients in Early Stages of Chronic Kidney Disease

Abstract: them from further complications and progression into severe stages of the disease. Studies on the estimates of people's knowledge of CKDu and their ability to identify the disease early and seek treatment are unknown in Sri Lanka. Knowledge is measured in this study comprises information acquired from authoritative sources such as the local health department. The items of knowledge displayed in posters and educational sessions were used to construct the questionnaire of 67 knowledge items. Methods: The study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, studies in Egypt have shown the harmful effect of cadmium and lead exposure on the kidney and the deterioration of kidney function correlating with increased metal levels 117 . Others have shown the contribution of environmental arsenic and cadmium exposure to CKD not related to diabetes and glomerulonephritis 118 . Environmental lead and cadmium exposure has been found to cause kidney damage and dysfunction in Senegal 119 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies in Egypt have shown the harmful effect of cadmium and lead exposure on the kidney and the deterioration of kidney function correlating with increased metal levels 117 . Others have shown the contribution of environmental arsenic and cadmium exposure to CKD not related to diabetes and glomerulonephritis 118 . Environmental lead and cadmium exposure has been found to cause kidney damage and dysfunction in Senegal 119 .…”
Section: Resultsmentioning
confidence: 99%
“…117 Others have shown the contribution of environmental arsenic and cadmium exposure to CKD not related to diabetes and glomerulonephritis. 118 Environmental lead and cadmium exposure has been found…”
Section: Ckd and Environmental Stressorsmentioning
confidence: 99%